Race strategies of young super-sprint triathletes during the 2022 World Triathlon races - Espejo, R.; Martinez-Sobrino, J.; Veiga, S. (International Journal of Performance Analysis in Sport, 2024)
Despite the increasing number of super-sprint events on the World Triathlon calendar over the last years, there is no scientific evidence about the performance determinants of this discipline. The present study described the race strategies of young international triathletes during super-sprint triathlon races and examined the influence of each segment on the final race outcome. Race data from the eight super-sprint triathlon events organised by World Triathlon in 2022 (all Continental Cups or Championships) were analysed for a total of 305 men and 268 women participants from junior and youth categories. Running performance showed the greatest correlation with finishing position (r = 0.89), followed by the cycling (r = 0.84) and swimming (r = 0.69) segments. Number of race packs increased through the race with no differences between males and females races. Medallists showed partial positioning within the Top-8 positions for the whole races and with gap times no longer than 12 seconds for both men and women. In addition, their running velocities were faster than the non-successful triathletes with no differences in the remaining race segments. Successful triathletes in super-sprint races seem to maintain a controlled gap from the race leaders during the swimming and cycling segments to optimise performance on the critical running segment.